2022
DOI: 10.1098/rstb.2021.0332
|View full text |Cite
|
Sign up to set email alerts
|

Avian cardiomyocyte architecture and what it reveals about the evolution of the vertebrate heart

Abstract: Bird cardiomyocytes are long, thin and lack transverse (t)-tubules, which is akin to the cardiomyocyte morphology of ectothermic non-avian reptiles, who are typified by low maximum heart rates and low pressure development. However, birds can achieve greater contractile rates and developed pressures than mammals, whose wide cardiomyocytes contain a dense t-tubular network allowing for uniform excitation–contraction coupling and strong contractile force. To address this apparent paradox, this paper functionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…Indeed, all birds are ectothermic in novo and achieve endothermy post‐hatching. Precocious species hatching birds that are feathered, as well as active and capable of finding their own food, reach endothermic thermoregulatory capacity at birth through the rapid development of aerobic capacity to withstand greater energy demands (Shiels, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, all birds are ectothermic in novo and achieve endothermy post‐hatching. Precocious species hatching birds that are feathered, as well as active and capable of finding their own food, reach endothermic thermoregulatory capacity at birth through the rapid development of aerobic capacity to withstand greater energy demands (Shiels, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of regeneration, repair and progression of some tumours could be part of the physiological adaptation to conditions of hypoxia (Cadiz & Jonz, 2020; Guenin‐Mace et al., 2023; Liu et al., 2022), thyroid regulation (Hirose et al., 2019), ecto‐endothermy (Cadiz & Jonz, 2020; Chang et al., 2009; Hirose et al., 2019; Jacob et al., 2021; Rennolds & Bely, 2023; Shiels, 2022), and epigenetics and chromatin organization (Palacios, 2019; Pillai et al., 2021) (Fig. 5).…”
Section: Introductionmentioning
confidence: 99%
“…One of the fruitful approaches may be a comprehensive analysis of epidemiologic, evolutionary, and cross-species studies [ 8 , 15 , 16 , 17 ]. Therefore, we compared the data of epidemiological studies concerning the diseases triggering the main causes of developmental programming of CVD, including growth retardation, inflammation, and malnutrition in babies, toddlers, and children [ 18 , 19 , 20 , 21 ], and the literature describing the data on developmental adaptation of cardiovascular system in more than 30 bird and 40 mammal species [ 14 , 22 , 23 , 24 , 25 , 26 ]. The data of epidemiological studies revealed early life gastroenteritis of various etiologies [ 18 , 20 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data of epidemiological studies revealed early life gastroenteritis of various etiologies [ 18 , 20 , 27 , 28 , 29 , 30 ]. Comparative cross-species analysis indicated that early life cardiac functional load can be an important trigger of the developmental programming of adult CVD, because it is inversely related to heart aerobic capacity in adults [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiomyocytes (CMs) are the main cellular components of the myocardium and are responsible for effectively executing the contraction-relaxation cycle of the heart. Although birds and mammals have the same heart structure with two atria and two ventricles, the control method for intracellular calcium ions (Ca 2+ ), the regulator of CM contraction-relaxation, differs greatly between them [1][2][3]. Mammalian CMs have T-tubule membranes which are invaginations of the cell membrane perpendicular to the direction of contraction [1,3,4].…”
Section: Introductionmentioning
confidence: 99%